Isolation and Characterization of Microcrystalline Cellulose Derived from Plants as Excipient in Tablet : A Review - Nagina Gulab Belali; Anis Yohana Chaerunisaa; Taofik Rusdiana (Universitas Padjadjaran (Unpad), 2019)
Microcrystalline cellulose (MCC) is a versatile and frequently used material in different industries such as pharmaceuticals production, medical, cosmetics, and food industry. Its qualities of being inert, economic, compatibility, compatibility, non-toxicity, biodegradability, good mechanical properties, high surface area, variety and availability of different grades and biocompatibility has made it very popular. Many research has been done on MCC to isolate it from different plant sources that are economical and eco-friendly. MCC is extracted from α cellulose that is abundant in nature as most of MCC is produced from wood. However, new eco-friendly sources with changes in methods of isolation have been applied for the production of MCC. In this review MCC isolated from different plant-based resources, extraction process parameters, the origin of raw material and its influence on critical material attributes of MCC has been outlined and discussed thoroughly. Since these critical material attributes have a significant effect on tablet making process parameters (compressibility, compatibility and etc) and its post-compression characters.Keywords: Microcrystalline cellulose, isolation, characterization, raw material, tablet